2014
DOI: 10.1158/0008-5472.can-13-1055
|View full text |Cite
|
Sign up to set email alerts
|

Neuregulin Autocrine Signaling Promotes Self-Renewal of Breast Tumor-Initiating Cells by Triggering HER2/HER3 Activation

Abstract: Currently only patients with HER2-positive tumors are candidates for HER2-targeted therapies. However, recent clinical observations suggest that the survival of patients with HER2-low breast cancers, who lack HER2 amplification, may benefit from adjuvant therapy that targets HER2. In this study, we explored a mechanism through which these benefits may be obtained. Prompted by the hypothesis that HER2/HER3 signaling in breast tumor-initiating cells (TICs) promotes self-renewal and survival, we obtained evidence… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
36
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 42 publications
0
36
0
Order By: Relevance
“…Increasing evidence links HRG/ErbB3 signaling to mammary tumorigenesis and metastasis. In addition, studies have assigned key roles to autocrine HRG-mediated activation of ErbB3/ErbB2 in sustaining tumor growth and conferring resistance to therapeutic agents (15,17,25,26,28,(72)(73)(74). The fact that ErbB3 signals primarily through activation of the PI3K pathway (1,7,8) invariably argues for a prominent role of the receptor in shifting the balance toward enhanced cell survival, invasiveness, and the maintenance of the tumor phenotype.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Increasing evidence links HRG/ErbB3 signaling to mammary tumorigenesis and metastasis. In addition, studies have assigned key roles to autocrine HRG-mediated activation of ErbB3/ErbB2 in sustaining tumor growth and conferring resistance to therapeutic agents (15,17,25,26,28,(72)(73)(74). The fact that ErbB3 signals primarily through activation of the PI3K pathway (1,7,8) invariably argues for a prominent role of the receptor in shifting the balance toward enhanced cell survival, invasiveness, and the maintenance of the tumor phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…SDF-1 activates the Rac1 small GTPase to promote breast cancer cell motility (40). Since elevated production of the ErbB ligand HRG occurs in a significant proportion of breast tumors (5,6,15,17), we decided to examine the effect of persistent HRG treatment on CXCR4-mediated Rac1 activation and motility in breast cancer cells. To this end, breast cancer cells (BT-474, MDA-MB-361, and MCF-7) were subjected to prolonged treatment with HRG (10 ng/ml; 16 h).…”
Section: Hrg Sensitizes Breast Cancer Cells To Sdf-1-induced Rac1 Actmentioning
confidence: 99%
See 1 more Smart Citation
“…Trials are currently under way to assess whether the endocrine therapy index of CTCs is correlated with patient outcome (28). Heterogeneous expression of the ERBB3 (HER3) and its ligand NRG1 have been reported in a variety of human cancers, including breast cancer, lung cancer, and glioblastoma (23,29,30). HER3 signals as heterodimer with other receptors of the HER family leading to potent activation of the PI3K/AKT pathway (22).…”
Section: Heterogeneity In Ligand/receptor Expressionmentioning
confidence: 99%
“…Although HER2 targeted therapies are currently only approved to treat patients with HER2-positive disease, analysis of results from two adjuvant trastuzumab (anti-HER2) trials revealed that patients with Her2-low tumors also benefit from adjuvant treatment (35,36). On the basis of these findings, Lee and colleagues explored the role of HER2 signaling in CSCs from Her2-low tumors and found that activation of HER2/HER3 by NRG1 autocrine signaling supports their proliferation and self-renewal (30). NRG1 alone is sufficient to support mammosphere formation by breast CSCs (37), and NRG1 also stimulates the growth of primary lung CSCs in sphere cultures (38).…”
Section: Heterogeneity In Ligand/receptor Expressionmentioning
confidence: 99%